Realization of the Right to Health Protection in Insurance Medicine: The First Experience of Covid-19 - Lutsyuk, Pavlo; Bolokan, Inna; Davydova, Iryna; Chanysheva, Alina; Yakymchuk, Svitlana (Ius Humani. Jornal do direito, 2020)
This article analyze the effectiveness of insurance medicine and the negative consequences of its work, which we could observe in the first period of the pandemic. The research methodology is based on general and special scientific methods, in particular: formal-legal, historical-legal, comparative analysis, and modeling. The procedure and issues to be considered are as follows: in the introduction, we will consider the concept of " the right to health care" and why it is important; in the first section, we will look at the general state of affairs, figures for different countries, and the first results of the fight against the pandemic; in the second section, we will touch on some of the problems of access to health care in the insurance system and its aggravation in connection with the pandemic; in the third, we will consider the impact of the pandemic on the health insurance system and how it could have been avoided some problems. The results of this study emphasize that the medical insurance system has extremely unsatisfactorily coped with the pandemic and its consequences, and therefore it is necessary at least to carry out a full-fledged official, and at best to develop an urgent comprehensive modernization program, taking into account the above positive experience of other developed countries.